2020
DOI: 10.1186/s12944-020-01312-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations of iron status with apolipoproteins and lipid ratios: a cross-sectional study from the China Health and Nutrition Survey

Abstract: Background: Iron overload has been found to be related with various cardiometabolic disorders, like dyslipidemia, metabolic syndrome, and diabetes. The disturbance of the iron status and lipid metabolism can contribute to organ damage such as atherosclerotic plaque growth and instability. An assessment on the associations of iron status with apolipoproteins and lipid ratios would be informative for maintenance of metabolic homeostasis and hinderance of disease progression. Hence, this study aims to establish t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 58 publications
3
6
1
Order By: Relevance
“…The inconsistent findings may be related to different animal models or iron handing. Increasing iron also did not affect serum Glu and lipid-related metabolites except for APOA, which was coincident with the previous study that iron status was negatively associated with APOA (Zhou et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…The inconsistent findings may be related to different animal models or iron handing. Increasing iron also did not affect serum Glu and lipid-related metabolites except for APOA, which was coincident with the previous study that iron status was negatively associated with APOA (Zhou et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…We also observed that the changes in ferritin were negatively associated with the changes in postprandial TG and the changes in fasting and postprandial apoCIII. These effects, which were independent of fructose and glucose consumption, are contradicted by a recent observational study showing fasting ferritin levels were positively associated with TG and lipoproteins [56]. This discrepancy may be due to the much higher ferritin concentrations exhibited by the subjects studied by Zhou et al They were divided into quartiles based on ferritin concentrations; only three of the subjects in our study met the criteria of the second-highest quartile and none fit in the highest quartile.…”
Section: Discussioncontrasting
confidence: 88%
“…In both sexes of a Chinese population, SF was associated with lipid parameters (including TC, LDL-C, TG, and HDL-C) independent of diabetes and IR ( 12 ). The previous study using the same cohort confirmed positive correlations of SF with dyslipidemia and unfavorable lipid ratios, especially apoB and non-HDL-C, independent of HOMA-IR ( 50 ). Notably, apoB and non-HDL-C are proven independent risk factors for CVD ( 51 ).…”
Section: Discussionsupporting
confidence: 58%